Pengaruh Career Planning, Self Efficacy dan Adversity Quotient Terhadap Kesiapan Kerja Mahasiswa S1 di Semarang: Career Planning Influence, Self-Efficiency and Adversity Quotient on The Work Readiness of S1 Students in Semarang - Rita Meiriyanti; Qristin Violinda; Wahyuningsih, Siti (School of Business, Bogor Agricultural University (SB-IPB), 2023)
This study aims to determine the effect of career planning, self-efficacy and adversity quotient on the job readiness of undergraduate students in Semarang. The object of this research is undergraduate students in Semarang who have entered the final semester with a sample of 100. The research was conducted using quantitative methods with purposive sampling as the specific criteria to be taken as samples. Data analysis technique with classical assumption test. The results of the study showed (1) there was a positive and significant influence on career planning on the job readiness of undergraduate students in Semarang with a tcount value of 2,457 > ttable 1,984 and a significance value of 0.016 <0.05, (2) not there is an effect of self efficacy on the work readiness of undergraduate students in Semarang with a tcount of 1.868 < ttable 1.984 and a significance value of 0.065 > 0.05, (3) there is a positive and significant influence of adversity quotient on work readiness of undergraduate students in Semarang with tcount 4.983 > ttable 1.984 and a significance value of 0.000 <0.05. (4) there is a positive and significant effect of career planning, self-efficacy and adversity quotient together on the work readiness of undergraduate students in Semarang with an Fcount of 57.959 > Ftebel 2.70 and a significance value of 0.000 <0.05. The coefficient of determination (R2) with an adjusted R square value of 0.633 means that the career planning, self-efficacy, and adversity quotient variables can explain the work readiness variable by 63.3% and 36.7% is influenced by other variables outside the study. Keywords: career planning, self efficacy, adversity quotient, work readiness